Reflective thinking among primary school students (Journal of the College of Basic Education, 2023)
The aim of the current research is to identify the level of primary school students' possession of reflective thinking. To achieve the goal of the research, a test consisting of (21) objective items was prepared and distributed over five skills, which are (observation and reflection, discovering fallacies, reaching conclusions, developing proposed solutions, and giving convincing explanations). The apparent validity of the test was calculated by presenting it to a group of arbitrators. And the experts and the validity of the internal consistency in the light of the following indicators (the relationship of the item score with the total score of the test, the relationship of the item with the skill attached to it). As for the reliability of the test, it was calculated using the Keuder-Richardson equation (K - R20), and it was applied in the academic year 2021-2022 on a sample of students The sixth grade of elementary school in the General Directorate of Education of Maysan Governorate, consisting of (260) students, applied the test for a period of three days, starting from Sunday corresponding to (3/20/2022), and the following statistical methods were used (difficulty coefficient, discrimination coefficient, effectiveness of wrong alternatives, Chi-square, T-test for one sample and for two samples) using the SPSS statistical package, and the following results were reached: There is a weakness in the level of possession of reflective thinking by primary school students. The two researchers recommended several recommendations, including: educating mathematics teachers of the importance of reflective thinking among students as one of the important goals of teaching mathematics, as well as qualifying and training them through training courses. Some proposals were also put forward, including: Conducting a study on the causes of difficulties in learning reflective thinking and the extent of their spread in Baghdad governorate or in other governorates.